Impact of different pathogen classes on the serum N-glycome in septic shock - Helena Torpy; The Huong Chau; Sayantani Chatterjee; Anastasia Chernykh; David J. Torpy; Emily J. Meyer; Morten Thaysen-Andersen (BBA Advances)
The morbidity and mortality of sepsis remain high. Clinicians lack effective markers to rapidly diagnose sepsis and identify the underlying pathogen infection particularly for patients with candidaemia or cases of culture-negative sepsis where culture-based diagnostics are inadequate. In our search for new lines of potential sepsis biomarkers, we here explore the impact of various classes of infectious agents on the serum N-glycome in a septic shock cohort. Comparative N-glycomics was performed on sera collected from 49 septic shock patients infected with viral (n = 9), bacterial (n = 37) or fungal (n = 3) pathogens using an established PGC-LC-MS/MS method. Aberrant serum N-glycosylation features were observed in patients with fungal infection relative to the other infection sub-groups including i) altered expression of prominent α2,6-sialylated biantennary N-glycan isomers, ii) elevated levels of IgG-type N-glycosylation and iii) a global shift in the serum N-glycome involving altered glycan type distribution and considerable changes in core fucosylation and α2,6-sialylation. Septic shock patients infected with bacterial and viral pathogens exhibited similar global serum N-glycome features and therefore could not be stratified based on their serum N-glycosylation. Subtle and less consistent serum N-glycome differences were observed between septic shock patients infected with different bacterial pathogens. In conclusion, our study has tested the impact of different pathogen classes on the serum N-glycome in a septic shock cohort, and reports that fungal infection impacts the host serum N-glycome differently compared to bacterial or viral infections thus potentially opening avenues for glycan-based biomarkers to better diagnose patients with candidaemia.